Interrelation among one-carbon metabolic (OCM) pathway-related indicators and its impact on the occurence of pregnancy-induced hypertension disease in pregnant women supplemented with folate and vitamin B12: Real-world data analysis - Zhang, Yanfei; Gu, Chenhong; Lei, Ying; Wang, Jingwen; Sun, Leiqin; Fan, Junwei; Wang, Yanlin; Zhang, Xiaoqing (Frontiers in Nutrition, 2023)
Background and objective A considerable number of pregnant women who were supplemented with folate and vitamin B12 were selected as major participants in studying the one-carbon metabolic (OCM) pathway. Our study aimed to explore the effects of OCM-related indicators on pregnancy-induced hypertension (PIH) and preeclampsia (PE) in pregnant women with folate and vitamin B12 supplementation. Subjects and methods A total of 1,178 pregnant women who took multivitamin tablets containing 800 μg folate and 4 μg vitamin B12 daily from 3 months before pregnancy to 3 months after pregnancy were enrolled in this study. These pregnant women were classified into three groups: the normotensive group (n = 1,006), the PIH group (n = 131), and the PE group (n = 41). The information on age, weight, body mass index (BMI), number of embryos, gravidity, parity, and OCM-related indicators (serum level of homocysteine, folate, and vitamin B12; MTHFR C677T genotype) was collected. Results The accuracy of the prediction model based on the screened independent risk factors (hyperhomocysteine, OR = 1.170, 95% CI = 1.061–1.291; high folate status, OR = 1.018, 95% CI = 0.999–1.038; and high BMI, OR = 1.216, 95% CI = 1.140–1.297) for PIH in subjects with MTHFR CC genotype (AUC = 0.802) was obviously higher than that in subjects with MTHFR CT, TT genotype (AUC = 0.684,0.685, respectively) by receiver operating characteristic curve analysis. The homocysteine level of the PIH group was significantly higher than that of the normotensive group only in subjects with the MTHFR CC genotype (p = 0.005). A negative correlation between homocysteine and folate appeared in subjects with MTHFR CT + TT genotype (p = 0.005). A model including multiple embryos, nulliparas, and lower folate could predict the process from PIH to PE (AUC = 0.781, p < 0.0001). Conclusion The prediction model composed of homocysteine, folate, and BMI for PIH was suitable for subjects with MTHFR CC genotype in pregnant women with supplementation of folate and vitamin B12. Lower folate levels could be an independent risk factor in developing the process from PIH to PE.